Nelarabine Associated Myotoxicity and Rhabdomyolysis - Mahnur Haider; Syed Ahsan Rizvi; Pashtoon Murtaza Kasi (Case Reports in Hematology)
Nelarabine (ara-G; Arranon; compound 506U78) is an antineoplastic purine analog used for the treatment of refractory or relapsed T-cell acute lymphoblastic leukemia (T-ALL) and T-cell lymphoblastic lymphoma (T-LBL). The drug was granted accelerated approval in October 2005 by the US Food and Drug Administration (FDA) given the efficacy (induction of complete responses) noted in 2 single-arm trials (one in pediatric setting and one in adult patient population). The main spectra of toxicities that have been reported in these clinical trials and subsequent studies are hematological and neurological. Nelarabine induced rhabdomyolysis and increased creatinine phosphokinase (CK; CPK) levels apparently have been reported and this side effect has been added as an adverse reaction in the product monograph from the drug company during postmarketing surveillance. However, the true extent and incidence of the myotoxicity from the drug are unclear. In this paper we report a grade IV CK elevation and rhabdomyolysis in a patient with T-ALL treated with nelarabine. Given the reported finding, we examined the literature further for myotoxicity, increased CK, and/or rhabdomyolysis associated with the use of the nelarabine and report our findings.